UPAYA DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA DALAM MENEGAKKAN RESOLUSI KONFLIK (Studi Kasus: Konflik Sudan dan Sudan Selatan Terkait Wilayah Heglig) - Rifial Febrianto Alit (Dauliyah: Journal of Islam and International Affairs, 2021)
In the International world, it is known as an element of conflict that occurs and involves an individual and state actor. In this case Sudan and South Sudan with a lot of background experienced conflict until finally the former two countries were one country, then separated and ran their respective countries. but when they separated they faced a conflict which was the Heglig region where the area was located south of Sudan, so it was prone to conflict from both. The actions of the attacks that took place in the Heglig area made the United Nations as an International Organization not silent. The United Nations which has a chart named the Security Council is involved in this conflict. The Security Council with its peace operation prioritizes Peace-making, Peacekeeping Operations, Enforcement of sanctions, and peace building in the final conflict can be enforced. Although in the end it got obstacles from some parties, for example China which tried to protect the two countries, but did not stop the Security Council from resolving the conflict. Conflict resolutions offered by the UN Security Council for Sudan and South Sudan are contained in the 2046 and 2075 Conflict Resolutions of 2012. Until where Sudan and South Sudan end and promise to obey the Resolution and the Heglig region to avoid war action. The efforts made by the Security Council were appreciated by the international community by seeing the success of the resolutions issued and effectively carried out by the parties concerned.